Plankton diversity in the Rowo Klampok Swamp, Malang District, East Java, Indonesia - DIANA ARFIATI; UMI ZAKIYAH; SEPTI ANITASARI; ZAKIYYAH NUR INAYAH; KHARISMA ORCHIDA; RIZKY KUSMA PRATIWI (Society for Indonesian Biodiversity, 2024)
Abstract. Arfiati D, Zakiyah U, Anitasari S, Inayah ZN, Orchida K, Pratiwi RK. 2024. Plankton diversity in the Rowo Klampok Swamp, Malang District, East Java, Indonesia. Biodiversitas 25: 1846-1855. Wetlands are a productive ecosystem and have high biodiversity, including plankton. Plankton can be used to assess the health status of wetlands. This research aims to determine the diversity and abundance of phytoplankton and zooplankton and to analyze the water quality conditions of the tropical wetland (Rowo Klampok Swamp, Malang District, East Java, Indonesia). This research was conducted from May to June 2023 and it's a survey research. The research results show that the phytoplankton found in Rowo Klampok Swamp consists of 4 divisions with 13 genera, while there are 3 divisions with 3 genera in zooplankton. Phytoplankton divisions are Bacillariophyta, Chlorophyta, Cyanophyta, and Dinoflagellate, while zooplankton divisions are Arthropoda, Ciliophora, and Rotifera. The average value of total phytoplankton abundance reached 2,618,684 cells/L, while zooplankton was 10,504 Ind/L. The Chlorophyta division is the most commonly found phytoplankton, with a percentage ranging between 32.5 and 53.1%, respectively. Dictyosphaerium is a phytoplankton genus often found with the highest average abundance of 1,922,929 cells/L. The diversity index, uniformity index, and dominance index of phytoplankton ranged between 1.965-2.439, 0.945-1.173, and 0.125-0.213, respectively, while those of zooplankton were 0.496-0.529, 0.317-0.593 and 0.458-0.684, respectively. Rowo Klampok Swamp has a medium trophic level (mesotrophic) and shows moderate pollution. The water quality conditions are considered suitable for aquatic organisms, but we need to monitor and reduce phosphorus input into the bodies of water.